When Is “Type I” Ovarian Cancer Not “Type I”? Indications of an Out-Dated Dichotomy - Salazar, Carolina; Campbell, Ian G.; Gorringe, Kylie L. (Frontiers in Oncology, 2018)
The dualistic classification of epithelial ovarian cancer (EOC) into “type I” and “type II” is widely applied in the research setting; it is used as a convenient way of conceptualising different mechanisms of tumorigenesis. However, this classification conflicts with recent molecular insights of the aetiology of EOC. Molecular and cell of origin studies indicate that while type II tumours could be classed together, type I tumours are not homogenous, even within the histological types, and can have poor clinical outcomes. Type II high grade serous carcinoma and type I low grade serous carcinomas best fit the description of the dualistic model, with different precursors and distinct molecular profiles. However, endometriosis-associated cancers should be considered a separate group, without assuming an indolent course or type I genetic profiles. Furthermore, the very clear differences between mucinous ovarian carcinomas and other type I tumours, including an uncertain origin, and heterogeneous mutational spectrum and clinical behaviour, indicate a non-type I classification for this entity. The impression that only type II carcinomas are aggressive, have poor prognosis and carry TP53 mutations is an unhelpful misinterpretation of the dualistic classification. In this review, we revisit the history of EOC classification, and discuss the misunderstanding of the dualistic model by comparing the clinical and molecular heterogeneity of EOC types. We also emphasise that all EOC research, both basic and clinical, should consider the subtypes as different diseases beyond the type I/type II model, and base novel therapies on the molecular characteristics of each tumour.